Evolution of the Product and Process Requirements during the Project Lifetime - Rudolf, Lukasz; Roszak, Marek; Kucharikova, Lenka (Communications - Scientific Letters of the University of Zilina, 2024)
The automotive industry, known for its dynamism and innovation, relies on effectiveness of product and process requirements management. Effective collaboration with OEM (Original Equipment Manufacturers) is essential for success. The article analyses how product and process requirements evolve during different project phases, following the APQP (Advanced Product Quality Planning) approach, depending on OEM type. The study focuses on Tier 1 organizations, direct suppliers to the automotive industry, and their diverse approaches to product development. It underscores the need for Tier 1 organizations to maintain flexibility in their operations and to be prepared for changes in OEM demands. The study emphasizes the role of effective communication and coordination among all the levels of the supply chain to ensure the successful implementation of the APQP approach.
Keywords: product requirements; process requirements; APQP; supply chain